Peran Hukum Lingkungan Hidup dalam Mewujudkan Pembangunan Berkelanjutan di Indonesia Terhadap Pencemaran Lingkungan - Iqbal, Muhammad F.; Aulya, Muhammad; Zulfikar, Muhammad A.; Noor, Rendy Febrian (PT Literasi Nusantara Publisher, 2024)
This article discusses the important meaning of environmental pollution protection and the concept of environmental law enforcement against polluters. This research is a normative juridical study using a legislative approach. The research findings indicate that the significance of environmental law in addressing pollution caused by industries is demonstrated in the efforts to achieve sustainable development in Indonesia, where environmental protection is considered as the foundation to achieve that goal. Awareness of the close relationship between law and sustainable development is the key to success. The concept of law enforcement consists of two main perspectives, namely civil law and criminal law. Civil law emphasizes compensation and absolute liability, while criminal law involves the process of investigation, prosecution, and implementation of judicial decisions. Criminal sanctions can be applied to individuals or legal entities, with an emphasis on deterrence and corporate responsibility. In conclusion, to enhance environmental law enforcement, the government needs to improve supervision and the implementation of criminal sanctions. Good coordination among relevant institutions, such as sectoral authorities, in granting permits and environmental monitoring is also crucial. The active role of the community in reporting environmental violations and supporting environmental conservation policies is highly necessary.